DETERMINASI PERSISTENSI LABA: Peran Volatilitas Penjualan, Arus Kas Operasi, dan Tingkat Hutang pada Sektor Properti dan Real Estate di Indonesia - Winingrum W. A., Sri Putri; Adinda, Nur Afiyah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Profit persistence can be interpreted as the possibility that a company's profit level will repeat itself in the future. This study aims to determine the effect of sales volatility (X1), operating cash flow (X2) and debt levels (X3) on profit persistence (Y) in Properties and Real Estate companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Sampling in this study used a purposive sampling technique and obtained 13 sample companies. The data analysis method used is quantitative data analysis, namely using panel data regression analysis and using the EViews 12 tool. The results of this study indicate that partially operating cash flow has an effect on earnings persistence. Meanwhile, sales volatility and debt levels partially have no effect on earnings persistence. Meanwhile, simultaneously sales volatility, operating cash flow and debt levels affect earnings persistence with an R2 contribution of 21.35%.